(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
This article is based on a talk presented by the first author at the conference on Lie and Jordan Algebras, their Representations and Applications held in Guarujá, Brazil in May 2004. The article surveys some recent progress by a number of authors in the study of extended affine Lie algebras and some closely related Lie algebras called Lie tori.